Graphic Memories of the Civil Rights Movement: Reframing History in Comics - Rocksborough-Smith, Ian (Labour / Le Travail, 2020)
The article reviews the book, "Graphic Memories of the Civil Rights Movement: Reframing History in Comics," by Jorge J. Santos, Jr .